Critical Inquiry on Institution of Museum; Relying on Merleau-Pontyꞌs Phenomenological Thoughts - Nader Shayganfar; Zeynab Saber (حکمت و فلسفه, 2015)
The French phenomenological philosopher, Maurice Merleu-Ponty, tried to understand art works and related concepts taking recourse to phenomenological approach. In the new point, he tried to understand art by emphasizing on the being- in-the-world relying on perception’s term and it’s relation to art. Based on the some of the concepts such as intentionality, living experiences, art style, establishing and etc. Merleu-Ponty wants to conceive a new interpretation from art. The museum is essential in Merleu-Pontyꞌs thoughts since it has deeply related with art affairs with relying on its history. The main question of this article is that how relation between lived experiences and museum is. Based on Merleu-Pontyꞌs vital philosophy, this article concerns phenomenologically to critic the role of museum and indicates that the meaning of phenomenological establishing and storing is different from what is aiming in museum. This study targets the questions of how much honest are the museums in storing as well as how much this honesty is influenced by the social and cultural elements.